A Correlation Between Health Service Quality and Patients Satisfaction at Lesung Batu Health Center in Empat Lawang Regency - Etika Etika; Fikitri Marya Sari; Wulandari Wulandari (Journal of International Public Health, 2026)
Intoduction: Health centers (Puskesmas) are required to improve the quality of services, not only providing curative services but also encompassing preventive services to enhance quality of life and provide satisfaction to consumers as healthcare users. This study aims to determine the correlation between health service quality and patient satisfaction at Lesung Batu Health Center in Empat Lawang Regency. Method: The method used was an analytical survey with a cross-sectional design. Primary data were collected by distributing questionnaires to 34 patients receiving treatment at the Lesung Batu Health Center in Empat Lawang Regency using accidental sampling. Data analysis was performed using the Chi-Square test. Result and Discussion: Univariate analysis results showed that more than half of patients (52.9%) stated that the quality of service was poor, and more than half (55.9%) stated that they were dissatisfied. Bivariate analysis results showed a significant correlation between health service quality and patient satisfaction (p=0.017). Conclusion: The researchers recommend that the Health Center improve its service quality to increase the number of patient visits and improve patient satisfaction with the services provided by the health center.